High-temperature pressure sensors with strain gauges based on silicon whiskers - Druzhinin, A. A.; Kutrakov, A. P.; Maryamova, I. I. (Technology and design in electronic equipment, 2012)
Studies aimed at the creating of piezoresistive pressure sensors based on silicon whiskers, operating at high temperatures were carried out. Using the glass adhesive for strain gauges mounting on spring elements of covar alloy gave the possibility to elevate the sensor’s operating temperature range. Several modifications of pressure sensors based on the proposed strain-unit design were developed.